Pengaruh Kualitas Produk, Diskon dan Tagline “Gratis Ongkir” terhadap Keputusan Pembelian Pada Market Place Shopee (Studi Kasus Pada Mahasiswa FEB, Universitas Muhammadiyah Metro) - Azizi, Ferdian; Yateno, Yateno (Universitas Muhammadiyah Metro, 2021)
Buying and selling online is a trend that has now penetrated the world of schools and campuses. The rapid development of internet technology has led to changes in behavior among the public and students, including students of the Muhammadiyah Metro University. The survey method was chosen as the primary data source. The survey method focuses on collecting data on respondents who have certain information, allowing researchers to solve problems. In this study, the population was FEB students of Muhammadiyah Metro University. The sampling technique used accidental sampling with a sample size of 75 people. The results showed that: there was a positive influence on product quality on purchasing decisions, there is a positive effect of discounts on purchasing decisions, there is a positive effect of the tagline “free shipping” on purchasing decisions, there is a positive effect on product quality, discounts and the tagline “free shipping” together on purchasing decisions.